Tata Kelola Pemerintahan dalam Pengembangan Desa Perbatasan : (Studi Penerapan Prinsip Good Governance di Desa Silawan, Kecamatan Tasifeto Timur, Kabupaten Belu) (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study aims to evaluate the implementation of Good Governance principles in the development management of Silawan Village, Tasifeto Timur Subdistrict, Belu Regency, located on the Indonesia–Timor-Leste border. The research focuses on aspects of participation, transparency, accountability, and effectiveness, as well as the supporting and inhibiting factors in their implementation. Using a qualitative approach, data were collected through observation, interviews, and document analysis. The results indicate that Good Governance principles have begun to be applied through community deliberations, budget transparency, and public oversight of village programs. Although governance has been relatively effective due to the support of community leaders and local infrastructure, challenges such as low citizen participation and slow response from the regency government remain significant obstacles.